2018
DOI: 10.1002/jcb.28159
|View full text |Cite
|
Sign up to set email alerts
|

A three microRNA‐based prognostic signature for small cell lung cancer overall survival

Abstract: Background Small‐cell lung cancer (SCLC) is one of the most aggressive cancers with mechanisms far from understood. Objective We proposed to identify valuable prognostic signature for SCLC prognosis prediction. Methods microRNA (miRNA) expression profiles of 42 SCLC patients were acquired from the Gene Expression Omnibus. miRNAs that significantly associated with SCLC overall survival (OS‐relevant) were identified through univariate Cox regression analysis followed by random survival forest analysis for identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Based on this fourteen-mRNA prognostic nomogram, we developed an online precision medicine predictive tool named the Smart Cancer Survival Predictive System, which can generate full-time mortality risk prediction curves for one specific patient at the individual level. Several prognostic models have been built for predicting the prognosis of lung cancer patients (Xie & Xie, 2019;Yan et al, 2018;Zuo et al, 2019). However, these previous prognostic models could only provide prognostic information for a special subgroup at the group level and failed to provide individual mortality risk prediction at the individual level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this fourteen-mRNA prognostic nomogram, we developed an online precision medicine predictive tool named the Smart Cancer Survival Predictive System, which can generate full-time mortality risk prediction curves for one specific patient at the individual level. Several prognostic models have been built for predicting the prognosis of lung cancer patients (Xie & Xie, 2019;Yan et al, 2018;Zuo et al, 2019). However, these previous prognostic models could only provide prognostic information for a special subgroup at the group level and failed to provide individual mortality risk prediction at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…Several prognostic models have been built for predicting the prognosis of lung cancer patients ( Xie & Xie, 2019 ; Yan et al, 2018 ; Zuo et al, 2019 ). However, these previous prognostic models could only provide prognostic information for a special subgroup at the group level and failed to provide individual mortality risk prediction at the individual level.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these prognostic www.nature.com/scientificreports www.nature.com/scientificreports/ expression signatures have been applied to clinical practice because of their uncertain performance on clinical samples. Furthermore, some studies were devoted to the excavation of prognostic markers from the perspective of microRNA or lncRNA profile, and a few prognostic signatures were proposed [24][25][26] ; however, their clinical performance remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al built a three‐miRNA signature (miR‐1293, miR‐873, and miR‐1914) of LUAD using the TCGA database. Yan et al also found a 3‐miRNA signature (miR‐194, miR‐608, and miR‐9) using 42 SCLC patients acquired from the GEO dataset. Zhang et al performed a high‐throughput polymerase chain reaction assay to obtained a five‐serum‐miRNA signature, serving as a predictor of advanced NSCLC patients' prognosis.…”
Section: Discussionmentioning
confidence: 99%